2017
DOI: 10.24127/ajpm.v6i2.1038
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Bahan Ajar Berbasis E Learning Pada Matakuliah Evaluasi Pembelajaran Untuk Meningkatkan Hasil Belajar Mahasiswa

Abstract: The ability to evaluate learning is a basic skill that must be mastered by students as prospective teachers. Based on this, it is necessary a teaching materials that help students and lecturers during the lecture. Students can know and understand about learning evaluation. In addition, the existence of teaching materials can help students to improve students' skills in understanding the material. In order for students to learn independently and adapt to technology, e-learning is needed based on teaching materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
6
0
4
Order By: Relevance
“…The results of the development through the stages of validation, practicality and effectiveness are carried out by two experts, namely media experts and material experts, teachers and students gave very satisfying results. (Vahlia 2017), (Yasa 2019), so it can be obtained that the results of the development of online teaching materials have met the valid, practical and effective criteria in learning process during the COVID-19 era. Based on the results of this research and development, it can be suggested as follows: (1) Teaching materials using flipbooks in science learning in elementary schools have been developed and the results are valid, practical, and effective in SD Negeri 32 Bungloe, Bantaeng Regency, so it is recommended to use them in elementary schools other.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the development through the stages of validation, practicality and effectiveness are carried out by two experts, namely media experts and material experts, teachers and students gave very satisfying results. (Vahlia 2017), (Yasa 2019), so it can be obtained that the results of the development of online teaching materials have met the valid, practical and effective criteria in learning process during the COVID-19 era. Based on the results of this research and development, it can be suggested as follows: (1) Teaching materials using flipbooks in science learning in elementary schools have been developed and the results are valid, practical, and effective in SD Negeri 32 Bungloe, Bantaeng Regency, so it is recommended to use them in elementary schools other.…”
Section: Discussionmentioning
confidence: 99%
“…Bahan ajar juga dalam pengembangan memperhatikan aspek kompetensi inti, salah satu kompetensi inti yang harus diperhatikan yaitu keterampilan, dimana hal ini penting untuk membantu peserta didik dalam berpikir tingkat tinggi. Pengembangan bahan ajar tersebut harus melakukan proses pemilihan, adaptasi, dan pembuatan yang berdasarkan kerangka acuan sesuai dengan analisis kebutuhan (Vahlia, 2017). Bahan ajar dalam pembelajaran membantu peserta didik untuk mencapai hasil yang optimal.…”
Section: Pendahuluanunclassified
“…Teaching materials must be present in the learning process because teaching materials are one of the complementary components of learning tools that must be prepared by teachers as educators (Khalil & Elkhider, 2016;Stockwell et al, 2015). Teaching materials must be designed completely in the sense that there are elements and learning resources that are following the characteristics of students so that they will affect the learning atmosphere which results in learning being more optimal (Risnawaty et al, 2021;Stockwell et al, 2015;Vahlia, 2017). Teaching materials are equipped with illustrations that can attract and produce a stimulus for students to use teaching materials as a source of learning.…”
Section: Introductionmentioning
confidence: 99%